La Aguadita Trachyte: New exponent of Triassic alkaline magmatism in Sierra de Valle Fértil, Western Sierras Pampeanas, Argentina - Castro, Brigida Marta Ester (2015)
La Aguadita Trachyte, in Sierra de Valle Fértil, is a new outcrop referring to the Triassic alkaline magmatism. The trachyte body was emplaced along a NNW-trending fault zone overlying the crystalline basement. The trachyte consists mainly of anorthoclase and sanidine as pheno- and microphenocrysts, with lesser amounts of arfvedsonite and ferro-eckermannite in the groundmass. It is moderately evolved in composition with 66.5-69.1 wt.% SiO2 and exhibits a limited compositional range in most of the major elements. The rare earth elements (REE) pattern is somewhat uniform and highly fractionated, being enriched in light REE over heavy REE and showing a prominent negative Eu anomaly. The trachyte is enriched in high field strength elements Nb, Zr, and Y, consistent with typical intraplate alkaline magmatism associated with continental rifting. It is proposed to be genetically linked to other alkaline volcanic rocks outcropping in the area, and generated from the same parental source (i.e., asthenospheric mantle source) through open-system fractional crystallization. ɛNd values of +2.6 are consistent with slightly crustal contamination during trachyte generation. Thus, La Aguadita Trachyte could be the result of a combination of fractional crystallization of mantle-derived basaltic magma and crustal assimilation. Radiometric age dating of 218 ± 7 Ma on the trachyte (K-Ar age, whole rock) expands the range of the alkaline volcanism known in the area to the Upper Triassic, and confirms a regional volcanic event related to uplift in an extensional tectonic environment.